1988
DOI: 10.1002/pen.760281502
|View full text |Cite
|
Sign up to set email alerts
|

The spin‐coating process mechanism related to polymer solution properties

Abstract: Coating the substrate with an amorphous polymer layer is a very common process in the manufacturing of integrated circuits, but the fundamental spin‐coating mechanism has not yet been precisely determined. This study examines the influence of the macromolecular characteristics on the spin‐coating process both experimentally and from a phenomenological point of view. It is concluded that the weight‐average molecular weight of the spun‐on solution is a pertinent parameter, and that chain entanglements in polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 9 publications
3
35
0
Order By: Relevance
“…Solutions 1, 3, and 4 were all prepared using xylene as a solvent and had the same concentration of 1.6% w/v. The effect of solution concentration was linked with the effect of solution viscosity by some researchers (Damon, 1966;Schwartz, 1965;Weill and Dechenaux, 1988). In their experiments, different viscosity solutions were obtained by varying the concentration of the same material.…”
Section: Figurementioning
confidence: 99%
“…Solutions 1, 3, and 4 were all prepared using xylene as a solvent and had the same concentration of 1.6% w/v. The effect of solution concentration was linked with the effect of solution viscosity by some researchers (Damon, 1966;Schwartz, 1965;Weill and Dechenaux, 1988). In their experiments, different viscosity solutions were obtained by varying the concentration of the same material.…”
Section: Figurementioning
confidence: 99%
“…From a n experimental standpoint, published work has dealt largely with the development of empirical correlations to relate a variety of different processing parameters to film thickness (3, 4,9,[17][18][19][20][21]. For example, it has been observed that rotational speed, solution viscosity, and solution concentration all significantly affect thicknesses, while amount of solution initially dispensed on the substrate provided the substrate is entirely covered, rate at which it is dispensed, rate at which final acceleration is achieved, and total spin time have negligible effects.…”
Section: Introductionmentioning
confidence: 99%
“…[21,29,30] Ellipsometric measurements taken on a null ellipsometer (Rudolph Research Auto EL) confirm that the increasing UV-vis absorbance observed for each bilayer corresponds to an increasing film thickness. [21,29,30] Ellipsometric measurements taken on a null ellipsometer (Rudolph Research Auto EL) confirm that the increasing UV-vis absorbance observed for each bilayer corresponds to an increasing film thickness.…”
mentioning
confidence: 97%